PENGEMBANGAN PRODUK PANGAN DENGAN SUBSTITUSI RED PALM OIL SEBAGAI ALTERNATIF PANGAN FUNGSIONAL TINGGI BETA KAROTEN - Marjan, Avliya Quratul; Marliyati, Sri Anna; Ekayanti, Ikeu (Jurnal Gizi dan Pangan, 2016)
The objective of this study was to develop a bagelen cookies with Red Palm Oil (RPO) substitution as an alternative of functional food high in beta carotene. Complete randomize design with level of RPO as a treatment was applied in this study to produce three substitution formulas and one basic formula. The selected bagelen was determined by sensory evaluation by considering the highest average value and level of RPO substitution. Bagelen with 42% Red Palm Oil (F3) was preferred by 70% panelist. This formula contained 3.11% water, 0.94% ash, 26.72% fat, 41.95% saturated fatty acids and 35.07% unsaturated fatty acids, 8.53% protein, 60.70% carbohydrate, 18.29 ppm (mg/kg) β-carotene, antioxidant activity 75.11% with AEAC value was 43.44 mg/100 g. With its high beta carotene as natural antioxidants, this product may be classified as functional food that are beneficial to health for preventing atherosclerosis.